The estimated solution is (x, y) = (2, -4)
The algebraic solution is (x, y) = [tex](\frac{9}{4} , \frac{-15}{4})[/tex]
Solution:
Given system of equations are:
3x + y = 3 ---- eqn 1
5x - y = 15 ------- eqn 2
Let us solve the above system of equations
Add eqn 1 and eqn 2
3x + y + 5x - y = 3 + 15
8x + 0 = 18
8x = 18
[tex]x = \frac{18}{8} = \frac{9}{4}[/tex]
[tex]x = \frac{9}{4}[/tex]
Substitute the value of "x" in eqn 1
[tex]3(\frac{9}{4}) + y = 3\\\\\frac{27}{4} + y = 3\\\\y = 3 - \frac{27}{4}\\\\y = \frac{12-27}{4}\\\\y = \frac{-15}{4}[/tex]
The estimated solution is given as:
Enter whole numbers for the estimated solution
[tex]x = \frac{9}{4} = 2.25\\\\x \approx 2[/tex]
[tex]y = \frac{-15}{4} = -3.75\\\\y \approx -4[/tex]
Thus estimated solution is (x, y) = (2, -4)
The algebraic solution is given as:
Enter improper fractions in simplest form for the algebraic solution
In an improper fraction, the numerator is always greater than or equal to the denominator
[tex]x = \frac{9}{4}[/tex]
[tex]y = \frac{-15}{4}[/tex]
Thus the solution is (x, y) = [tex](\frac{9}{4} , \frac{-15}{4})[/tex]